The Influence Of Transportation Service Quality On Customer Satisfaction With Trans Padang Bus Service Users - Della Asmaria Putri; Putri Azizi; Yosi Puspita Sari (Profesional Muda Cendekia Publishing, 2022)
The purpose of this study was to determine how much influence Tangibles, Reliability, Responsiveness, Assurance, Emphaty on Customer Satisfaction at Trans Padang Bus Service Users. Methods of data analysis using a questionnaire, with a sample of 100 respondents. The data analysis method used is Multiple Linear Regression Analysis. Based on the research results show that Tangibles, Reliability, Responsiveness, Assurance, Emphaty have a positive and significant effect on Customer Satisfaction. The Tangibles, Reliability, Responsiveness, Assurance, Emphaty variable contribution has an effect of 66.1% while the remaining 33.9% is influenced by other variables outside of this study. Based on the results of this study, it is hoped that the Management of the Company can increase Customer Satisfaction, where in this study the Reliability variable has a dominant influence on Customer Satisfaction of Trans Padang Bus Service Users, so it is advisable to pay more attention to the problem of Reliability, because it has a dominant influence on Customer Satisfaction of Service Users. Trans Padang Bus.